Analisis Faktor-Faktor Yang Mempengaruhi Keputusan Membeli Komoditi Pertanian Di Pasar Tradisional Kepanjen Malang - Bayu, Indra; Ibrahim, Jabal Tarik; Bakhtiar, Ary; Mufriantie, Fithri (AGRIBEST, 2020)
A market is a meeting place for sellers and buyers who are conducting transactions, both goods, and services. One of the main items for buying and selling activities is agricultural commodities as the main source of food. One of the most found and popular markets is the traditional market. The purpose of this research is to analyze together the influence of product factors, income, quantity, quality of place, service on the decision to buy agricultural commodities in the traditional Kepanjen market, and which factors are the most dominant. The sampling technique used accidental sampling, with the number of respondents 88 and multiple linear regression. The results of the research are the characteristics of the respondents are dominated by the female gender, ranging in age from 36-55, having a family of 3-4 people, junior high school education, and with an income ranging from 2,500,000 to 4,000,000. The results of the F test analysis obtained a significance value of 0.119, which means that there is a joint influence on the variables of income, quantity, quality of place, service on the decision to buy agricultural commodities in the traditional Kepanjen market. While the t-test obtained two variables that have a value less than 0.15, namely the quantity variable 0.140 and the service variable 0.016 which means that it is partially influential and the most dominant is the service variable which influences the decision to buy agricultural commodities in the traditional market of Kepanjen Malang.Â